2015
DOI: 10.1055/s-0035-1559772
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Adaptation to Sport-specific Loading in Adolescent Athletes

Abstract: Tendon adaptation due to mechanical loading is controversially discussed. However, data concerning the development of tendon thickness in adolescent athletes is sparse. The purpose of this study was to examine possible differences in Achilles (AT) and patellar tendon (PT) thickness in adolescent athletes while considering age, gender and sport-specific loading. In 500 adolescent competitive athletes of 16 different sports and 40 recreational controls both ATs and PTs were sonographically measured. Subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
(41 reference statements)
1
21
0
2
Order By: Relevance
“…Waugh et al (2014) investigated the effects of a strength training intervention on the mechanical properties of the Achilles tendon in pre-pubertal children and reported a significant increase of tendon stiffness. More recently, a cross-sectional comparison of tendon thickness between 500 adolescent athletes from different sports provided an indication of tendon plasticity in response to increased loading for the patellar tendon as well (Cassel et al, 2016). Earlier work of our group already suggested that the patellar tendon is responsive to mechanical stimulation, but it was not possible to differentiate the effects of mechanical loading and maturation (Mersmann et al, 2017) or to directly compare the mechanical properties of the patellar tendon between athletes and controls due to inhomogeneous sample composition with regard to sex (Mersmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Waugh et al (2014) investigated the effects of a strength training intervention on the mechanical properties of the Achilles tendon in pre-pubertal children and reported a significant increase of tendon stiffness. More recently, a cross-sectional comparison of tendon thickness between 500 adolescent athletes from different sports provided an indication of tendon plasticity in response to increased loading for the patellar tendon as well (Cassel et al, 2016). Earlier work of our group already suggested that the patellar tendon is responsive to mechanical stimulation, but it was not possible to differentiate the effects of mechanical loading and maturation (Mersmann et al, 2017) or to directly compare the mechanical properties of the patellar tendon between athletes and controls due to inhomogeneous sample composition with regard to sex (Mersmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…17 However, the effect of puberty is unclear as no significant difference in patellar tendon thickness was found in prepubertal vs postpubertal 13-year-old athletes. 18 Mechanically, Achilles tendon stiffness was greater for post-PHV adolescent males compared to a pre-PHV group. 19 In a cross-sectional study, the proximal tendon attachment in participants who were less than 1 year post-peak height velocity had variable appearance on grayscale ultrasound, while those who were more than 1 year post-PHV had a grayscale appearance similar to mature participants between 21 and 40 years of age.…”
Section: Introductionmentioning
confidence: 90%
“…Patellar tendon thickness has been positively correlated with age in 11‐ to 15‐year‐old volleyball players . However, the effect of puberty is unclear as no significant difference in patellar tendon thickness was found in prepubertal vs postpubertal 13‐year‐old athletes . Mechanically, Achilles tendon stiffness was greater for post‐PHV adolescent males compared to a pre‐PHV group .…”
Section: Introductionmentioning
confidence: 97%
“…These differences most likely represent the wide variance of tendon load in different sport disciplines with a higher prevalence’s in explosive jumping sports. Therefore, volleyball and soccer can be considered high risk disciplines for tendon pathologies [ 20 ].…”
Section: Discussionmentioning
confidence: 99%